Screening of a Ti-46Al-2Cr-8Nb-xW alloy system through high energy ball milling and spark plasma sintering - Lim, Tedric Jie Ming (Nanyang Technological University, 2025)
Compositionally graded and discrete Ti-46Al-2Cr-8Nb-xW alloys containing up to 1 atomic % (at%) tungsten (W) were fabricated using high energy ball milling (HBM) from elemental powders consolidated by spark plasma sintering (SPS) and subsequently heat-treated. The influence of increasing W addition on the microstructure, phases and mechanical properties of the sintered samples were studied. An equiaxed fine-grained microstructure was formed, with increasing sparsity in lamellar microstructures with increasing W addition. Desired phases of TiAl and Ti3Al were observed to have formed in both as SPS and heat-treated samples. An increase in W concentration from 0 at% to 1 at% led to a 10.64% increase in hardness from 560HV to 620HV for the compositionally graded as SPS samples, and a 15.42% increase from 528HV to 609HV for the compositionally graded heat-treated samples. Fracture toughness of heat-treated discrete samples displayed a 32.9% decrease from 11.09MPa m1/2 to 7.44MPa m1/2, with the composition containing 0 at% W possessing the highest fracture toughness. This shows that while W additions can be beneficial to the room temperature mechanical hardness, room temperature fracture toughness decreases. At 0.6 at% W, the sample showed a slight 2.4% increase in hardness, with a minimal 3.4% decrease in fracture toughness. The results also show that this alloy composition has the potential for further investigation.